Effects of EDTA and Phosphate Concentrations on Sandstone Permeability: A Multiple Linear Regression Analysis - Bayu Satiyawira; Mustamina Maulani; Andry Prima; Cahaya Rosyidan; Lisa samura; Havidh Pramadika; Puri Wijayanti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Permeability determines how readily fluids can move through reservoir rock, and any reduction caused by formation damage may directly affect well productivity. This study examined the effect of a completion fluid containing EDTA (ethylenediaminetetraacetic acid) and sodium phosphate (Na₃PO₄) on sandstone permeability and evaluated the experimental results using multiple linear regression. Laboratory tests were performed on two sandstone core plugs, S-1 and S-2, with initial effective oil permeabilities (Ko) of 9.9784 mD and 13.4409 mD and porosities of 19.52% and 19.23%, respectively. Three fluid formulations were tested: CF-1 (5% phosphate + 10% EDTA), CF-2 (10% phosphate + 10% EDTA), and CF-3 (15% phosphate + 10% EDTA). After each injection, the samples were aged for 24 hours, and permeability was measured with a Hassler Core Holder using a modified form of Darcy's law. The regression analysis produced the model Y = 0.148 + 1.476X₁ + 5.447X₂, with R² = 0.9794 and an F-statistic of 71.37 (p < 0.0001). Within the model, phosphate accounted for an estimated 78.7% of the permeability improvement, while EDTA accounted for 21.3%. The highest Ko values were obtained with CF-3: S-1 increased from 9.9784 to 19.4885 mD (+95.31%), and S-2 increased from 13.4409 to 26.0651 mD (+93.92%). Incremental improvement decreased from an average of 40.15% at CF-1 to 23.71% at CF-2 and 12.26% at CF-3, indicating diminishing marginal gains at higher phosphate concentrations. Porosity remained unchanged during the injection sequence, suggesting that the increase in permeability was associated with the removal of material restricting pore throats rather than an increase in pore volume. These results support the potential use of the phosphate-EDTA system for formation treatment and completion-fluid optimization within the tested concentration range.